The effect of mechanical and chemical polishing techniques on the surface roughness of heat-polymerized and visible light-polymerized acrylic denture base resins - Abdul Aziz Abdullah Al-Kheraif (Saudi Dental Journal)
Objective: The purpose of this study was to compare the effects of mechanical polishing (MP) and chemical polishing (CP) on the average surface roughness (Ra) of heat-cured (HC) and light-cured (LC) denture base acrylic resins. Methods: A total of 120 specimens (30 × 15 × 3 mm) were prepared from one HC and one LC acrylic resin. To remove nodules and gross surface irregularities, all specimens were finished with a lathe-mounted small acrylic bur and 360-grit sandpaper. Ten finished specimens of each acrylic resin were randomly assigned to each of six polishing techniques: Resilit High-luster Polishing Liquid (RHPL), Universal Polishing Paste, Abraso-star K50, pumice, Jet Seal Liquid, or Acrypoint. MP was performed with an automatic polishing machine for 2 min, under 50 rpm and 500 g of load. CP was performed by immersing the HC and LC specimens in preheated methyl methacrylate at 75 ± 1 °C for 10 s. The surface roughness of the acrylic resin specimens was measured with a contact profilometer. The Ra values were analyzed by two-way analysis of variance, post hoc Scheffe's test, and paired t-test (p ⩽ 0.05). Polished and tested acrylic resin surfaces were evaluated by scanning electron microscopy. Results: MP was more effective than CP. The smoothest surface was obtained with the use of the RHPL on the LC (0.05 ± 0.01 μm) or HC (0.07 ± 0.01 μm) acrylic resin. Two-way ANOVA showed a statistically significant difference between MP and CP. Conclusions: MP produced the smoothest surface of denture base acrylic resin. The mean surface roughness values after MP and CP were not influenced by the type of acrylic resin. Keywords: Surface roughness, Mechanical polishing, Chemical polishing, Contact profilometer, Acrylic resin